9-Silafluorene and 9-germafluorene: novel platforms for highly efficient red phosphorescent organic light-emitting diodes. Issue 30 (20th July 2018) - Liu, Xiang-Yang; Tian, Qi-Sheng; Zhao, Danli; Ran, Quan; Liao, Liang-Sheng; Fan, Jian
Abstract : De novo molecular platforms have been applied to build host materials for highly efficient PHOLEDs. A 9-silafluorene derivative was studied for the first time as a host and an external quantum efficiency of over 28% was achieved successfully in red PHOLEDs. Abstract : Two novel heterofluorene motifs consisting of the group 14 elements Si and Ge were developed as robust molecular platforms for the construction of organic light-emitting diode (OLED) materials. These two compounds exhibited similar photophysical properties, thermal stabilities and electrochemical behaviors except for the charge transport abilities. The red OLED hosted by a 9-silafluorene derivative (DPS) with Ir(MDQ)2 (acac) as the emitter exhibited state-of-the-art current efficiency, power efficiency, and external quantum efficiency (EQE) with maxima of 50.7 cd A −1, 44.7 lm W −1, and 28.3%, respectively. In addition, the maximum EQE of a 9-germafluorene derivative (DPG)-based red device could reach 20%. These results indicated the great potential of group 14 element derivatives in the construction of highly efficient OLED materials.